NO PAIN IS A PATIENT’S GAIN – A REVIEW OF SURGICAL TECHNIQUES FOR PREVENTION AND TREATMENT OF POSTAMPUTATION PAIN - Georgieva, Gordana; DJokikj, GJorgje; Dzonov, Boro; Pejkova, Sofija (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2022)
Regardless of the cause, major lower limb amputation is a life-changing event and accompanied by pain it has a great impact on patients’ quality of life. Over the years many pharmacological and surgical treatments have been tried to manage residual limb pain and phantom limb pain, but they were either unsuccessful or did not apply to all patients. The aim of this review paper was to describe the current modalities of treatment of postamputation pain and the opportunity to use surgical techniques as prophylactic. More than 150 surgical interventions have been described in the literature: traction neurectomy, nerve capping, end-to-end nerve coaptation, nerve transposition, etc. New and efficient techniques are regenerative peripheral nerve interface and targeted muscle reinnervation initially described for bioprosthetic control. Results from recent studies have shown that these techniques can be used for treatment, but also in a prophylactic manner, which can only be of benefit for the patient.
Keywords: phantom limb pain; residual limb pain; neuroma; amputation; RPNI